2002
DOI: 10.1207/s15324796abm2401_07
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of self-perceptions of spirituality in American adults

Abstract: To advance knowledge in the study of spirituality and physical health, we examined sociodemographic, behavioral, and attitudinal correlates of self-perceptions of spirituality. Participants were a nationally representative sample of 1,422 adult respondents to the 1998 General Social Survey. They were asked, among other things, to rate themselves on the depth of their spirituality and the depth of their religiousness. Results indicated that, after adjustment for religiousness, self-perceptions of spirituality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 17 publications
7
95
0
1
Order By: Relevance
“…Streib et al (2009), on the basis of extensive empirical research, observe that across cultural boundaries and religious traditions, people may describe themselves as ''equally religious and spiritual, more religious than spiritual, more spiritual than religious,'' or ''neither religious nor spiritual,'' and that this may shift according to personal history and socialization, critical life events, and important developmental transitions interacting with periods in the life cycle. The same authors observe that most respondents described themselves as religious and spiritual, in keeping with the findings of Zinnbauer et al (1997), Cook et al (2000), Shahabi et al (2002), and Corrigan et al (2003). Together, these researchers observe that despite the contrasting positions of religion and spirituality in a small minority of subjects, and the use of ''spiritual'' as an explicitly anti-religious term in an even smaller subgroup of this minority, spiritual growth is viewed as something that can and does occur in what most subjects perceive to be the highly supportive framework of religion.…”
Section: Religious Development and Spiritual Development: Defining Thsupporting
confidence: 77%
“…Streib et al (2009), on the basis of extensive empirical research, observe that across cultural boundaries and religious traditions, people may describe themselves as ''equally religious and spiritual, more religious than spiritual, more spiritual than religious,'' or ''neither religious nor spiritual,'' and that this may shift according to personal history and socialization, critical life events, and important developmental transitions interacting with periods in the life cycle. The same authors observe that most respondents described themselves as religious and spiritual, in keeping with the findings of Zinnbauer et al (1997), Cook et al (2000), Shahabi et al (2002), and Corrigan et al (2003). Together, these researchers observe that despite the contrasting positions of religion and spirituality in a small minority of subjects, and the use of ''spiritual'' as an explicitly anti-religious term in an even smaller subgroup of this minority, spiritual growth is viewed as something that can and does occur in what most subjects perceive to be the highly supportive framework of religion.…”
Section: Religious Development and Spiritual Development: Defining Thsupporting
confidence: 77%
“…This interpretation is consistent with Eckersley's ( 2007 ) remark that spirituality is most commonly represented via religion which typically involves an institutionalized process of worshipping a higher being. This perspective is also consistent with fi ndings indicating that those who consider themselves religious also tend to report being spiritual (Joshanloo 2010 ;Shahabi et al 2002 ) . An alternative explanation may be that South Africans incorporate into their lives high levels of both religiousness and spirituality, perceived as two separate constructs which are developed through different mechanisms and behaviors.…”
Section: Discussionsupporting
confidence: 85%
“…In line with these observations, Shahabi et al (2002) found that in their representative sample (N = 1422) of the US population, 52% of respondents identified themselves as 'both spiritual and religious'. This group had a higher frequency of attending church services, praying, meditating, reading the Bible, and having daily spiritual experiences than the other three groups (10% 'onlyspiritual', 9% 'only-religious', and 29% 'neither spiritual nor religious').…”
Section: Spirituality: Opposing or Complementing Religion?mentioning
confidence: 54%